Using Teacher Presence in Online Higher Education to Foster Global Citizenship among Adult Learners - Tanya M. Tarbutton; Lori B. Doyle (Athens Institute for Education and Research, 2023)
Higher education institutions must recognize the responsibility to support online adult learners as members of a larger global community and technological advancements have made this a reality. COVID-19 restrictions to in-person learning highlighted the need for online learning platforms that promote the benefits of teacher presence, consider the tenets of the Community of Inquiry model, and commit to the principles of andragogy. A need to explore the possibilities for fostering global citizenship among adult learners in online higher education environments has been identified as a problem space and a methodological approach will be used to connect findings from the literature with best practices for practitioners. Global citizenship is not a new concept; however, current and worldwide events have created a renewed dedication to the construct. Discussions based on the literature and established theoretical frameworks will precede practical implications for directors, course designers, and instructors. Online education will be described as ripe with opportunities for higher education institutions to foster global citizenship among adult learners.